Penyelesaian Perselisihan Hubungan Industrial Melalui Mediasi Antara Karyawan Dengan Perusahaan Kopi Cap Kijang Bogor - Maria Veronica Ngadien Prawesti; Muhammad Rizal (Pusat Riset dan Inovasi Nasional, 2024)
Settlement of industrial relations disputes through mediation is a process of resolving conflicts between employees and the company with the help of a neutral mediator. The mediator acts as an impartial party and tries to facilitate dialogue between the two parties to reach a mutually beneficial agreement. Mediation in industrial relations can be an effective way to resolve disputes because it gives the parties involved greater control over the outcome than if decisions were made through arbitration or court processes. The purpose of this writing is to discuss the resolution of industrial relations disputes through mediation between employees and the Bogor Kijang Cap coffee company. The writing method used by the author is descriptive qualitative with case studies. The results of this research are that through effective mediation, problems in the industrial environment can be resolved in a fair and peaceful manner, creating a more harmonious and productive work environment for all parties involved. The agreements that have been made must be implemented carefully by both parties. This may involve changes in company policy, changes to employment contracts, or other actions necessary to ensure resolved issues do not re-emerge.